Answering Teachers’ Questions at the Esl (English as a Second Language) Conference, Badu Island, 15-18 May 2000 - Shepherd, Susan (The Australian Journal of Indigenous Education, 2003)
Abstract In 2000 a program of English as a Second Language inservice provision was initiated by the Thursday Island State High School in response to teacher and community concerns about low literacy rates in Torres Strait, as measured by the National Languages and Literacy Institute of Australia Bandscales and other related difficulties. In mid-May of that year an English as a Second Language conference was held on Badu Island and was attended by teachers from throughout Torres Strait. During the conference, Susan Shepherd (Education Adviser English Language Acquisition at Thursday Island State High School) conducted a question-and-answer session dealing with some of the most commonly asked questions: What is English as a Second Language teaching? What is an English as a Second Language learner? What is an English as a Second Language school? Why is the students’ English not improving in my school? Can we have learning support teachers? Why shouldn’t the children’s home language be banned from the school so that the students will learn English more quickly? Why can’t the children understand more about what they read? Why, if the local Creole is so much like English, do we need special programs in English?